Active Immunization Against hIAPP Oligomers Ameliorates the Diabetes- Associated Phenotype in a Transgenic Mice Model. Issue 1 (December 2017) - Bram, Yaron; Peled, Sivan; Brahmachari, Sayanti; Harlev, Michael; Gazit, Ehud
Abstract Type 2 diabetes is characterized by insulin tolerance in target cells followed by a reduction of pancreatic β-cell mass. Islet amyloid polypeptide oligomeric assemblies were shown to contribute to β-cell apoptosis by forming discrete pores that destabilize the cellular membrane. We previously characterized α-helical cytotoxic islet amyloid polypeptide oligomers which interact with cell membranes, following a complete internalization that leads to cellular apoptosis. Moreover, antibodies which bind the oligomers and neutralize the cytotoxicity were exclusively identified in the serum of type 2 diabetes patients. Here, we examined the usage of the newly characterized oligomers as an active immunization agent targeting amyloid self- assembly in a diabetes-associated phenotype transgenic mice model. Immunized transgenic mice showed an increase in hIAPP-antibody serum titer as well as improvement in diabetes-associated parameters. Lower fasting blood glucose levels, higher insulin, and lower islet amyloid polypeptide accumulation were observed. Furthermore, antibodies derived from the immunized mice reduced hIAPP oligomers cytotoxicity towards β-cells in a dose-dependent manner. This study highlights the significance of targeting the early amyloid self-assembly events for potential disease management. Furthermore, it demonstrates that α-helical oligomers conformers are valid epitope for the development of future immunization therapy.